Pemanfaatan Asesmen Diagnostik Untuk Merancang Kegiatan Pembelajaran Dengan Pendekatan Tarl - Larasati Nur Rachma; Supriyono Supriyono; Ninik Djoehartini (Departement of Mathematics Education, 2024)
Diagnostic assessments provide a detailed picture of how well students understand the standards being taught, which helps teachers develop learning techniques that better suit students' needs. The purpose of writing the article is to determine the level of ability of class VIII students at SMP Negeri 6 Semarang and then use it as a reference for readers, especially teachers and principals, to prepare teaching modules. The research approach used in this research is qualitative research. Based on the research results obtained, it is proven that the use of diagnostic assessments is important in measuring students' initial understanding so that teachers can analyze students' difficulties. Using diagnostic assessments makes it easier for teachers to determine and design learning concepts because they can be adapted to students' conditions. By using the Quizziz platform, teachers obtain student ability results more quickly. Of the 31 students who took the quiz, they got an average of 79.6%.